Peran Pendidikan Kewarganegaraan di Era Globalisasi dalam Menumbuhkan Semangat Nasionalisme Mahasiswa - Koesmiyati, Endang (Jurnal Likhitaprajna, 2021)
The growth of science and technology that is increasingly modern lately demands a high morality and understanding of nationalism, because science and knowledge that is not accompanied by a high level of nationalism and morality causes education, especially civic education loses its virtue as a humanist forum. Not a few people have good citizenship knowledge and outstanding academic achievements but do not provide significant benefits in their community, even become a source of problems for the community which is very dangerous for the existence of culture and human values because of the spirit of nationalism and low morality. Negative effects of globalization such as immoral cases committed by students in universities and intellectuals, as we have known through television broadcasts and mass media lately. It illustrates that the education carried out so far has not touched the realm of student awareness.